Prepectoral Direct-to-Implant Breast Reconstruction: Early Outcomes and Analysis of Postoperative Pain. Issue 1 (27th February 2019) - Fredman, Rafi; Wu, Cindy; Rapolti, Mihaela; Luckett, Daniel; Fine, Jason; McGuire, Kandace; Gallagher, Kristalyn; Roughton, Michelle
Abstract: Background: Direct-to-implant (DTI) breast reconstruction provides high-quality aesthetic results in appropriate candidates. Most commonly, implants are placed in the subpectoral space which can lead to pain and breast animation. Surgical and technological advances have allowed for successful prepectoral implant placement which may eliminate these trade-offs. Objectives: Here we present early outcomes from 153 reconstructions in 94 patients who underwent prepectoral DTI. We sought to determine whether these patients have less postoperative pain and narcotic use than subpectoral implant or expander placement. Methods: A retrospective review was performed for all prepectoral DTI reconstructions at our institution from 2015 to 2016. Data were collected on postoperative pain and narcotic use while in hospital. Results: The average follow-up time was 8.5 months (range, 3–17 months) and the overall complication rate was 27% ( n = 41) with the most common complications being skin necrosis (9%, n = 13) and infection (7%, n = 11). No statistically significant difference in complications was found in patients who underwent postmastectomy radiation therapy. Patients who underwent prepectoral DTI reconstruction did not have a statistically significant difference in postoperative pain and narcotic use while in-hospital compared with other techniques. Conclusion: Prepectoral DTI reconstruction provides good results with similar complication rates to subpectoral techniques. Prepectoral DTI eliminates the problem of breast animation. Although our series did not reach statistical significance in pain scores or requirement for postoperative narcotics, we believe that it is an important preliminary result and with larger numbers we anticipate a more definitive conclusion. Level of Evidence: 4: